Relation Between Platelet Reactivity Levels and Diabetic Retinopathy Stage in Patient with Type 2 Diabetes Mellitus by Using Multiplate Whole Blood Aggregometry. (18th August 2021) - Karagöz, Işıl Kutlutürk; Karagöz, Ali; Özkalaycı, Flora; Doğan, Cem; Kocabay, Gonenc; Elbay, Ahmet
ABSTRACT: Purpose : To test the hypothesis of a possible association between platelet reactivity and the severity of diabetic retinopathy using Multiplate whole blood aggregometry in type 2 diabetes mellitus patients. Methods : Of 157 patients were divided to three groups based on the severity of diabetic retinopathy (normal, non-proliferative and proliferative [ordinal among group 1-2-3]). Platelet reactivity was measured using arachidonic acid response to the ASPI and ADP platelet test. The association between DR stage and the degree of platelet reactivity (predictor variable) ASPI, ADP, systolic blood pressure, age, hypertension, body mass index (BMI), HbA1c, creatinine, Microalbumin, platelet, triglyceride/HDL and Hscrp variables were evaluated using ordinal logistic regression models (Model 1). The association between DR presence (outcome variable (group 1 vs group 2 and 3)) and the presence of variables was evaluated using binary logistic regression models (Model 2). Results : A comparison of the laboratory parameters of the three groups revealed that the ASPI, ADP, glucose and HbA1c values were significantly higher in Group-3 than Group-1. ASPI (odds-ratio OR: 1.044[1.021–1.09], p < .001], ADP (OR: 1.033[1.010–1.10], p : 0.002] and HbA1c (OR: 2.42(1.22, 4.94), p < .001) were demonstrated to be associated with stage of DR while the other variables were not. In binary logistic regression (model-2) analysis; ASPI (OR: 1.061[1.031–1.1], p < .001], ADP (OR: 1.03(1.01, 1.06), p : 0.045] and HbA1c (OR: 4.37 (1.67, 11.36)], p : 0.002) were associated with DR while the other variables were not. Conclusion : Herewith, we demonstrated that higher platelet reactivity measured by multiplate ASPI and ADP was significantly associated with stages of DR. Therefore, these measurements may be useful to predict the severity of DR in the clinical practice of physicians.